Religious Orientation and Subjective Well-being: The Mediating Role of Meaning in Life - You, Sukkyung (Journal of psychology and theology, 2019)
The present study concerns the relationship between religious orientation, meaning in life, and subjective well-being, as well as the mediating influence of meaning in life on the relationship between religious orientation and subjective well-being. Gender differences in this relationship are also examined. The subjects of the study were 579 university students (33.5% male; Mage = 21.98, SDage = 4.33). Intrinsic religious orientation was found to be a significant predictor of subjective well-being via meaning in life in both the male and female groups. Furthermore, extrinsic religious orientation was found to be a significant predictor of subjective well-being via meaning in life in the female group only.